The Synergy of Local Wisdom and National Education Policy: A Literature Review on Character Building in Indonesian Early Childhood Education - Elly Purwanti; Siti Khomsiyati (Indonesian Journal of Education and Youth Development, 2026)
This integrative literature review explores the synergy between local wisdom (kearifan lokal) and national education policy in shaping character building within Indonesian Early Childhood Education (ECE). Drawing upon 19 peer-reviewed articles published between 2015 and 2026, the study examines how indigenous cultural practices, such as traditional games, folklore, and arts, serve as pedagogical vehicles for realizing the character dimensions outlined in the Profil Pelajar Pancasila and the Kurikulum Merdeka. The findings reveal that project-based learning and ethnopedagogical approaches successfully bridge top-down policy with grassroots cultural realities. However, significant barriers remain, including insufficient teacher competency in culturally responsive pedagogy, a lack of localized teaching materials, and epistemological tensions between universalized developmental standards and diverse indigenous values. The review concludes by advocating for strengthened school-community partnerships, the development of culturally sensitive assessment metrics, and a decolonized paradigm that honors Indonesia's cultural plurality as its primary educational asset.